Konsep Tuhan di Dalam Al-Quran - Hairul Anwar (LP2M Universitas PTIQ Jakarta, 2015)
The concept of God is not a new concept in human civilization. Before Islam came, the name Allah had been used by the Arabs as the highest name of God among the other gods they worshiped. Of course the name of Allah does not just appear in their time, but has been known from the religions first, especially the hanif (straight) religion of the prophet Ibrahim. This paper tries to describe the origin of the name of Allah from the historical side, then puts it in the context of the Koran, so that it becomes clear the series of names of Allah from the beginning as god’s names are perceived in various forms and then returned by Islam to actual proportions and clean or proportionally purified. God is ultimately the One God who is incomparable and above all. The approach used by the author in this analysis is an analysis of the historical side and interpretation of the Koranic text.